Meningkatkan Komitmen Organisasi Bank Syariah: Peran Pemberdayaan dan Etika Kerja Islam - Arif, Muhammad; Zulkifli, Zulkifli; Firdaus, Firdaus; Hamzah, Zulfadli; Alfani, Mufti Hasan; Nuraini, Putri; Sudianto, Sudianto (UIR Press, 2025)
This research is important to conduct in order to fill the gap in previous studies related to human resource issues in Islamic banks, particularly in the city of Pekanbaru. The purpose of this study is to analyze the impact of employee empowerment and Islamic work ethics on the organizational commitment of employees at Islamic banks in Pekanbaru. This study is a causal research with a quantitative approach. The population of this study consists of 941 employees of Islamic banks in Pekanbaru, with a sample size of 273 employees. The research instrument is a questionnaire distributed randomly, and the data analysis method uses Smart PLS 3.0 software. The result of this study show that Islamic work ethics and employee empowerment have a positive impact on organizational commitment in Islamic Bank. The limitation of this study lies in the quantitative approach with survey method, which cannot delve deeper into the qualitative aspects of the influence of employee empowerment and Islamic work ethics on organizational commitment.